2016
DOI: 10.1186/s40902-016-0072-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydroxyapatite on critical-sized defect

Abstract: BackgroundXenologous or synthetic graft materials are commonly used as an alternative for autografts for guided bone regeneration. The purpose of this study was to evaluate effectiveness of carbonate apatite on the critical-size bone defect of rat’s calvarium.MethodsThirty-six critical-size defects were created on 18 adult male Sprague-Dawley rat calvaria under general anesthesia. Calvarial bones were grinded with 8 mm in daimeter bilaterally and then filled with (1) no grafts (control, n = 10 defects), (2) bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 26 publications
(28 reference statements)
3
21
4
Order By: Relevance
“…Our results are in agreement with the general assumption that HA has no osteoinductive activity [ 30 , 31 ] and in defects filled with HA alone, healing process largely depends on the osteoconductive properties of the material. Similar results have been reported by many authors [ 32 - 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with the general assumption that HA has no osteoinductive activity [ 30 , 31 ] and in defects filled with HA alone, healing process largely depends on the osteoconductive properties of the material. Similar results have been reported by many authors [ 32 - 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study did not show any statistically significant difference between the 2 groups at 8 and 12 weeks, but unlike the results at 8 weeks, the bone formation ability of Bio-Oss ® showed a slightly increasing tendency compared to Tio-oss ® at 12 weeks. This showed a similar trend with the study results by Kim et al [ 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies also reported that synthetic OCP and OCP-based material are highly biodegradable, and these reports showed a similar trend with our results [ 33 , 47 , 48 ]. A study by Kim et al, analyzed the products Bio-Oss ® and Bongros ® (Bio@ Inc., Seongnam, Korea) at 4 and 8 weeks after surgery, and it was observed that Bio-Oss ® (28.5%) showed less bone formation than Bongros ® (42.9%) at 4 weeks, but at 8 weeks, Bio-Oss ® (54.1%) showed more bone formation than Bongros ® (50.9%) [ 49 ]. The results of this study did not show any statistically significant difference between the 2 groups at 8 and 12 weeks, but unlike the results at 8 weeks, the bone formation ability of Bio-Oss ® showed a slightly increasing tendency compared to Tio-oss ® at 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The porous structure of HA promotes the ingrowth of cells and microvessel growth leading to bone formation. Moreover, for this bone material, optimal pore sizes from 150 to 500 μm are an important factor in forming new bone [ 2 ].…”
Section: Introductionmentioning
confidence: 99%